Evaluation of DNA Extraction Methods and Bioinformatic Pipelines for Marine Nano- and Pico-Eukaryotic Plankton Analysis - Muñoz-Colmenero, Marta; Sánchez, Ana; Correa, Begoña; Figueiras, Francisco G.; Garrido, Jose L.; Sotelo, Carmen G. (Frontiers in Marine Science, 2021)
The smallest size fractions of plankton, nano- and pico-plankton, have been highlighted due to they accomplish key functions in marine ecosystems. However, the knowledge about some of them is scarce because they are difficult or impossible to be detected and identified with non-DNA-based methodologies. Here we have evaluated five DNA extraction protocols (MT1-MT5) and seven bioinformatic pipelines (P1-P7) to find the best protocol for detecting most of the eukaryotic species of nano- and pico-plankton present in an environmental sample using Ion Torrent technology. The protocol MT3 was the most reproducible methodology, showing less variation among samples, good DNA quality and sufficient quantity to amplify and sequence the eukaryote species, offering the best results after sequencing. For bioinformatic analyses, P1 and P7 resulted in the highest percentage of detection for the difficult-to-detect species in mock communities. However, only P1 avoided the confusion with other closed species during the taxonomic assignment. The final protocols, MT3-P1 (free) and MT3-P7 (private), showed good and consistent results when they were applied to an environmental sample, being a valuable tool to study the eukaryotes present in environmental samples of nano- and pico-plankton, even for the genera that are difficult to be detected by other techniques.